Mutation analysis of TRPS1 gene including core promoter, 5'UTR, and 3'UTR regulatory sequences with insight into their organization - Solc, Roman; Klugerova, Michaela; Vcelak, Josef; Baxova, Alice; Kuklik, Miloslav; Vseticka, Jan; Beharka, Rastislav; Hirschfeldova, Katerina (Clinica chimica acta, 2017)
The TRPS1 protein is a potent regulator of proliferation, differentiation, and apoptosis. The TRPS1 gene aberrations are strongly associated with rare trichorhinophalangeal syndrome (TRPS) development. We have conducted MLPA analysis to capture deletion within the crucial 8q24.1 chromosomal region in combination with mutation analysis of TRPS1 gene including core promoter, 5'UTR, and 3'UTR sequences in nine TRPS patients. Low complexity or extent of untranslated regulatory sequences avoided them from analysis in previous studies. Amplicon based next generation sequencing used in our study bridge over these technical limitations. Finally, we have made extended in silico analysis of TRPS1 gene regulatory sequences organization. Single contiguous deletion and an intragenic deletion intervening several exons were detected. Mutation analysis revealed five TRPS1 gene aberrations (two structural rearrangements, two nonsense mutations, and one missense substitution) reaching the overall detection rate of 78%. Several polymorphic variants were detected within the analysed regulatory sequences but without proposed pathogenic effect. In silico analysis suggested alternative promoter usage and diverse expression effectivity for different TRPS1 transcripts. Haploinsufficiency of TRPS1 gene was responsible for most of the TRPS phenotype. Structure of TRPS1 gene regulatory sequences is indicative of generally low single allele expression and its tight control.
Keywords: DNA vazebné proteiny; dospělí; Base Sequence; 5' nepřekládaná oblast; Female; dítě; předškolní dítě; transkripční faktory; Adult; Haploinsufficiency; mladý dospělý; ženské pohlaví; mutační analýza DNA; sekvence aminokyselin; lidé; 3' nepřekládaná oblast; Transcription Factors; DNA Mutational Analysis; 3' Untranslated Regions; Amino Acid Sequence; haploinsuficience; Male; 5' Untranslated Regions; Child, Preschool; Young Adult; Langerův-Giedionův syndrom; sekvence nukleotidů; DNA-Binding Proteins; Child; promotorové oblasti (genetika); mužské pohlaví; Promoter Regions, Genetic; Langer-Giedion Syndrome; Humans